Benefits of freewriting for academic staff engaged in writing retreat - Castle, J. (South African Journal of Higher Education, 2017)
Increasing pressures on academics, particularly early-career academics, to conduct research and complete higher degrees has led many institutions to offer writing retreats that focus on the end product of academic writing, typically a journal article based on a chapter of their thesis. These ‘product-oriented’ retreats give little attention to the creative processes involved in writing, including becoming a generative and confident writer. This article focuses on freewriting as a creative process in a ‘process-oriented’ writing retreat which enables the benefits of freewriting to be shared among participants. Analysis of three freewrites completed by academics during a retreat shows that focused freewriting can engage academics in re-imagining doctoral study. These academics’ writing shows clearly the attributes and benefits of freewriting.